1990
DOI: 10.1103/physreva.42.6443
|View full text |Cite
|
Sign up to set email alerts
|

Observation of doubly excited resonances in theHion

Abstract: Laser photodetachment on a relativistic H beam has revealed several series of resonances in which both electrons are excited. These "bound states in the continuum" appear as dips in the partial production cross sections of various excited states of neutral hydrogen. We present here a detailed account of the experimental observation of the resonances and the results of fits of the measured yields to sets of Fano profiles. A simple analytic formula for the energy-level spacing in this quantum-mechanical three-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Electronic correlation studies in highly doubly excited atoms in the different situations schematically described above have been reported previously. These range from the pure three-body Coulomb systems He [4,5] and H [6] to non-Coulombic ones involving electronic collision excitation in He [7,8] and sequential laser excitation of both electrons in alkaline-earth-metal atoms [9 -15]. To overcome the autoionization broadening of the lines, dou- presence of weak I =k+1 components on both sides of the main I =k line, which corresponds to the selected 6snk state.…”
mentioning
confidence: 99%
“…Electronic correlation studies in highly doubly excited atoms in the different situations schematically described above have been reported previously. These range from the pure three-body Coulomb systems He [4,5] and H [6] to non-Coulombic ones involving electronic collision excitation in He [7,8] and sequential laser excitation of both electrons in alkaline-earth-metal atoms [9 -15]. To overcome the autoionization broadening of the lines, dou- presence of weak I =k+1 components on both sides of the main I =k line, which corresponds to the selected 6snk state.…”
mentioning
confidence: 99%
“…Both were members of an A ¼ þ1 series of Feshbach resonances. Later, Harris et al (1990) showed that many A ¼ þ1 resonances of 1 P o symmetry lie below each of the H(n=5-8) thresholds. For example, the window resonances shown in Fig.…”
Section: Article In Pressmentioning
confidence: 98%
“…If the attraction is not quite strong enough to form a Feshbach resonance, a "shape" resonance can exist above the level of the parent state if the additional electron's orbital angular momentum I is greater than or equal to 1 shape resonances exist. Their technique was further applied at even higher energies to explore several resonance phenomena including doubly excited states [8,9].…”
Section: Introductionmentioning
confidence: 99%